A Scientific Investigation into the Impact of CVT Roller Weight on Fuel Efficiency and Engine Performance in Motorcycles - Setiawan, M. Yasep; Hidayat, Nuzul; Purwanto, Wawan; Putra, Dwi Sudarno; Arif, Ahmad; Fernandez, Donny; Susanto, Edy; Baharudin, Agus (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
This research investigates the impact of Continuously Variable Transmission (CVT) roller weight on fuel consumption and engine performance in motorcycles. The study involved experimental testing of motorcycles fitted with rollers of varying weights (9 grams and 12 grams) to evaluate their effects on fuel consumption, and overall engine performance. This study concludes that the choice of CVT roller weight significantly affects both fuel consumption and engine performance, with potential implications for optimizing motorcycle efficiency based on user preferences and riding conditions. This study found that the 9-gram roller produced greater torque and power (7.85 Nm at 3,500 RPM, 8.45 hp at 6,500 RPM) than the 12-gram roller, but its fuel consumption was higher at low RPM (SFC 0.07 kg/hp.h at 1,500 RPM).